Efektifitas Isi Rumen Sapi Dapat Mengubah Tepung Dedaunan Menjadi Media Dan Maggot (Hermetia illucens), Organiknya Di Buat Pelet Ikan Lele Dumbo (Clarias gariepinus B) - Syahrizal, Syahrizal; Arifin, M Yusuf; Yulfiperius, Yulfiperius; Yulintine, Yulintine; Fathurrachman, M (Universitas Batangahari Jambi, 2025)
Quality feed can be made from plant-based formulations using bacterial decomposers and maggot bioconversion. This study aims to analyze the effectiveness of cattle rumen contents (CRC) in converting leaf meal from cassava leaves (Manihot utilissima), tarum leaves (Indigofera zollingeriana), and lamtoro leaves (Leucaena leucocepphala) into maggots.The organic media and maggots from a 21-day cycle of BSF (Black Soldier Fly) flies were used to make African catfish (Clarias gariepinus B) pellets. A completely randomized design (CRD) was used with 4 treatments and 3 replications, with treatment A (RFU 0.00%); B (IRS 5.0% : C (IRS 10.0%), D (IRS 15.0%). The results of this study are the best initial and final proximate average of organic media raw materials in C and D respectively (protein 20.00%; and 20.15%) and (36.70% and 36.5%). The best proximate pellet feed is also in C and D (protein 30.75% and 31.55% with energy 313.58 and 310.57 grams/Kcal.). The weight of pellets obtained A (862 grams), B (821 grams), C (792 grams) and D (629 grams) with the buoyancy of pellets for each treatment A. 34.11 minutes, B. 36.89 minutes, C. 38.11 minutes and D. 39.67 minutes. Pellets obtained from the highest organic media production in treatment B (570.53 grams) followed by A (567.07 grams), the best maggot biomass was in D (60.59 grams) followed by C (42.60 grams) with ESE (organic substrate efficiency) conversion values in treatments A (5.49%), B (4.91%), C (7.10%) and D (10.10%). For the average weight of the best individual maggots in treatment A (0.26 grams/tail), followed by B (0.22 grams), the lowest D (0.18 grams/tail) and the best individual maggot length in treatment A (1.55 cm), followed by B (1.15 cm) and the lowest C (0.93 cm). The count of the best individual maggots was C (1107 tails/600 grams) and D (969 tails/600 grams), followed by B (530 tails/600 grams) and A (526 tails/600 grams)